Family Support and Quality of Life for Chronic Kidney Disease (CKD) Patients Hemodialysis Therapy at Undata Hospital - Hasnidar Hasnidar; Muhammad Wahyu Aswadi; Windu Unggun Cahya Jalu Putra (Journal of Health and Nutrition Research, 2022)
Terminal kidney disease is used by government agencies such as the Heath Care Financing Administration (HCFA) which is a synonym for advanced stage chronic kidney failure. Hemodialysis action indirectly affects the quality of life of a patient which includes physical health, psychological condition, spirituality, socioeconomic status and family dynamics experiencing anxiety, stress and even depression. The purpose of the study was to analyze the relationship between family support and the quality of life of patients with chronic kidney disease (CKD), undergoing hemodialysis therapy at Undata Hospital Palu. The research design used is descriptive analytic with a cross sectional approach. The independent variable is family support and the dependent variable is the quality of life. Data analysis using chi square statistical test, significant value 0.05. The results showed that there was a relationship between family support and the quality of life of CKD patients in the hemodialysis unit of RSUD Undata Palu with p value = 0.000. The conclusion of this study is that there is a significant relationship between family support and the quality of life of CKD patients in the hemodialysis unit of RSUD Undata Palu. It is recommended that nurses can increase the role of nurses in terms of increasing education to patients and their families regarding hemodialysis actions